Pengaruh Gaya Kepemimpinan, Pelatihan dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor BPJS Ketenagakerjaan Cabang Banjarmasin - Sunardy Syahid; Bahar Sinring; Nur Alam Umar (Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT This study aims to analyze the influence of leadership style, training, and work motivation on employee performance at the Banjarmasin Branch of the BPJS Ketenagakerjaan Office. The study used a quantitative approach with a survey method. The study population was all 30 employees of the Banjarmasin Branch of the BPJS Ketenagakerjaan Office. Due to the relatively small population, the sampling technique used saturated sampling (census) so that the entire population was included as respondents. Data collection was conducted through questionnaires, while data analysis used multiple linear regression analysis with the help of SPSS Release 27. The results of the study indicate that leadership style, training, and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. Keywrds: Leadership style, training, work motivation, and employee performance